Recovery of Aluminum from Industrial Waste (Slag) by Melting and Electrorefining Processes - Ali, Maytham Mahmood; Yassen, Rabiha Saleh (Al-Khwarizmi Engineering Journal, 2018)
Slag of aluminum is a residue which results during the melting process of primary and secondary aluminum production. Salt slag of aluminum is hazardous solid waste according to the European Catalogue for Hazardous Wastes. Hence, recovery of aluminum not only saves the environment, but also has advantages of financial and economic returns. In this research, aluminum was recovered and purified from the industrial wastes generated as waste from both of State Company for Electrical and Electronic Industries (Baghdad/AlWaziriya) and General Company for Mechanical Industries (Babylon/-Al-Escandria). It was found that these wastes contain tiny proportions of other elements such as iron, copper, nickel, titanium, lead, and potassium. Wastes were recovered for green sustainability, saving energy and cost effectiveness. The method applied for recovering aluminum was pyro-metallurgical method by smelting and refining. X-Ray fluorescence spectroscopy and X- Ray diffraction techniques of the slag sample were used to determine the chemical analysis and phases, respectively. Melting experiments were conducted by using different types of fluxes (KAlF4, NaCl, KCl and AlCl3) at different percentages (0, 5, 10 %) and different melting temperatures (700, 750, 800oC). Design of Experiment (DOE) by Taguchi method, orthogonal array L9, was used in melting experiments. Melting efficiency of aluminum was equal to 84.7%. Electro-refining of aluminum was done by using anhydrous aluminum chloride and NaCl as ionic liquids at low temperature 100 ◦C in electro-refining method producing aluminum of 99% purity.